O programa de educação em tempo integral da prefeitura municipal de Vitória : contribuições para a avaliação de suas implicações na gestão escolar implicações na gestão escolar - Mota, Cristina Nascimento da (2013)
In this research we analysed the Full-Time Education (FTE) program, of Vitória City Hall, that extends the school day and acts through partnerships with several sectors of the society. We sought to comprehend the implications of this program for the school management evidencing points such as: the implementation process of the Integral Education program in school; the relation between the regular school time and the Full-Time Education; the use of the school/ s physical spaces for the Full-Time Education; the school and the partner institutions of the Integral Education program and the public investment in Full-Time Education. For this purpose, we verified the views of the program management team in schools and of the general coordinator that acts in the Education Secretariat. We used the case study as a research method and for the data processing we used research of qualitative and quantitative nature. A closed research questionnaire was applied to the managers with the Likert-type scale, following the Rasch model of reasoning scale, and for the FTE coordinators, an open research questionnaire. We carried out a document analysis and an interview with the general coordinator of this program. We drew on academic literature about the FTE, especially: Cavaliere (2003; 2007; 2009 and 2010); Coelho (2004; 2009 and 2011); Maurício (2009a; 2009b). We bring up for discussion the relation between public and private in education, the redefinition of the role of the State and the civil society and the importance of the school management in the current context. As theoretical supply for these discussions, we carried on a dialogue with the authors: Dourado (2011); Bruno (2008); Gramsci (2000); Przeworski (1995); Bobbio (2004); Peroni (2003, 2009, 2010); Giddens (2001); Gohn (2008); Paro (2005, 2010); Krawczyk (1999, 2000), among others. We/ ve noticed this program has been, in general, well evaluated by the participant subjects, however there are several implications pointed by these subjects, such as: the FTE fragmentation in regular school time and extra time in school; the lack of school space and infrastructure; the politics focused on socially vulnerable children; the lack of guiding curricular support for the Full-Time schools. Moreover, the partnerships haven t been enough to assist the needs of the schools inserted in the program, therefore, demanding a high level of organization for this articulation and for administrating some inner conflicts resulting from disputes for these spaces, what creates difficulties for the program management team in schools and in the Education Secretariat